(untitled) (Annals of Medical Research, 2021)
Aim: Diabetes mellitus is closely associated with many types of cancer including hepatocellular carcinoma (HCC). Alpha feto protein is still used as a biomarker for HCC worldwide but relation between type 2 diabetes mellitus (T2DM) and AFP is unclear. We aimed to investigate relations between AFP, T2DM and metabolic markers in this study.Material and Methods: 208 HCC patients were enrolled to study. 50 patients had T2DM (T2DM+HCC) and 158 patients were non-diabetic (NDM+HCC). 50 healthy people enrolled to the study as control group. Serum AFP levels were compared between healthy control group, T2DM+HCC group and NDM+HCC group. Serum AFP levels were compared with age, BMI, HgbA1c, fasting plasma glucose level (FPG), serum insulin level and insulin resistance (HOMA-IR).Results: AFP levels were higher in T2DM + HCC group patients according to healthy control group (p0,01). Mean AFP level was 201.97 ± 1093,89 in NDM + HCC group and 43.73 ± 85.67 in T2DM + HCC group. AFP levels were significantly higher in NDM + HCC group according to T2DM + HCC group (p0.05). Serum AFP levels were negatively correlated with increasing age and FPG (p0.05). Conclusion: HCC is an aggressive tumour that usually develops on cirrhotic liver and AFP levels are important for the diagnosis of HCC. Our study showed AFP levels could be significantly lower in the presence of T2DM. This study showed AFP could not be a reliable marker in cirrhosis for screening or diagnosis of the HCC in patients with T2DM.